The role of tumor inflammatory component of the tumor microenvironment of the endometrioid adenocarcinoma of the corpus uteri in different disease outcomes - D. A. Zinovkin (ABV-press, 2016)
This article presents data on the role of tumor associated T cells, B cells, natural killer cells, macrophages and dendritic cells in the prognostic value of the endometrioid adenocarcinoma. Furthermore, there was determining of its role in the early (up to 3 years) progression of the disease.